IFPRI Malawi Monthly Maize Market Report, February 2023 - Banda, Chimwemwe (International Food Policy Research Institute, 2023)
The Monthly Maize Market Report was developed by researchers at IFPRI Malawi with the goal of providing clear and accurate information on the variation of maize prices in selected markets throughout Malawi. The reports are intended as a resource for those interested in maize markets in Malawi, namely producers, traders, consumers, policy makers, and other agricultural stakeholders.